(untitled) (Swiss Medical Weekly, 2024)
AIM OF THE STUDY: The purpose of the present study was to evaluate demographic characteristics of inmates in the Canton of Zurich (exposure), and investigate the changes in diseases and drug use between 2015 and 2020 (outcome). METHODS: The study prospectively evaluated 51,989 inmates admitted to the Police Prison Zurich in Switzerland between 1 April 2015 and 31 August 2020 and who were systematically medically assessed. A total of 19,027 (37%) inmates had one or more health conditions, which the authors recorded according to the International Classification of Diseases-10 (ICD-10), in addition to demographic data (country of origin, sex, age, year of imprisonment), as well as details of any drugs used (type and dosage). RESULTS: The 19,027 inmates with medical conditions had a mean age of 35.4±12.5 years (range 10–89) and comprised 16,489 males (87%). The inmates originated from 170 countries, including 4606 from Switzerland (24.2%), 4227 from Eastern Europe (22%) and 3432 from the Middle East & North Africa (18%). A total of 1631 inmates (9%) were enrolled in the medication-assisted treatment (MAT) programme, and 672 patients (4%) received a psychiatric evaluation. The proportions of foreign prisoners did not increase during the study period. There was a significant increase in the use of antipsychotics from year 1 to 5 (y = 0.866x; R2 = 0.902; p = 0.01) and anticonvulsants from year 1 to 4 (y = 1.27x; R2 = 0.823; p = 0.01), and a significant decrease in the use of analgesics from year 2 to 5 (y = -4.42x; R2 = 0.947; p = 0.03) and antianxiety drugs from year 1 to 4 (y = -3.31x; R2 = 0.989; p = 0.005). Inmates from Switzerland were most likely to use antianxiety drugs, while inmates from the Middle East & North Africa were most likely to use antipsychotics (OR 2.09; CI 1.88–2.34) and anticonvulsants (OR 3.52; CI 2.90–4.29), whereas inmates from Latin and North America were most likely to use herbal medicine (OR 1.50; CI 1.05–2.10). CONCLUSIONS: The findings of this study could help anticipate needs of prisons as well as improve treatment of disease and assist with substance use or abuse, particularly in the context of migration.